mGluR1-Dependent Long Term Depression in Rodent Midbrain Dopamine Neurons Is Regulated by Neuregulin 1/ErbB Signaling - Ledonne, Ada; Mercuri, Nicola Biagio (Frontiers in Molecular Neuroscience, 2018)
Increasing evidence demonstrates that the neurotrophic factor Neuregulin 1 (NRG1) and its receptors, ErbB tyrosine kinases, modulate midbrain dopamine (DA) transmission. We have previously reported that NRG1/ErbB signalling is essential for proper metabotropic glutamate receptors 1 (mGluR1) functioning in midbrain DA neurons, thus the functional interaction between ErbB receptors and mGluR1 regulates neuronal excitation and in vivo striatal DA release. While it is widely recognized that mGluR1 play a pivotal role in long-term modifications of synaptic transmission in several brain areas, specific mGluR1-dependent forms of synaptic plasticity in substantia nigra pars compacta (SNpc) DA neurons have not been described yet. Here, firstly we aimed to detect and characterize mGluR1-dependent glutamatergic long-term depression (LTD) in SNpc DA neurons. Secondly, we tested the hypothesis that endogenous ErbB signalling, by affecting mGluR1, fine-tunes glutamatergic synaptic plasticity in DA cells. We found that either pharmacological or synaptic activation of mGluR1 causes a LTD of AMPAR-mediated transmission in SNpc DA neurons from mice and rat slices, which is reliant on endogenous NRG1/ErbB signalling. Indeed, LTD is counteracted by a broad spectrum ErbB inhibitor. Moreover, the intracellular injection of pan-ErbB- or ErbB2 inhibitors inside DA neurons reduces mGluR1-dependent LTD, suggesting an involvement of ErbB2/ErbB4-containing receptors. Interestingly, exogenous NRG1 fosters LTD expression during minimal mGluRI activation. These results enlarge our cognizance on mGluR1 relevance in the induction of a novel form of long-term synaptic plasticity in SNpc DA neurons and describe a new NRG1/ErbB-dependent mechanism shaping glutamatergic transmission in DA cells. This might have important implications either in DA-dependent behaviors and in learning/memory processes or in DA-linked diseases.